Role of focused Ultrasound in the diagnosis of Acute Appendicitis in Pediatric population. Selection of a standard diagnostic criterion - R, Sayani; SM, Mustahsan; AAS, Ali; M, Anwar (International Journal of Endorsing Health Science Research, 2015)
Objective To evaluate the diagnostic role of focused ultrasound of right iliac fossa in clinically suspected cases of acute appendicitis in pediatric population and its value as a standard diagnostic tool in that age group Material and Method A retrospective, cohort study was conducted at radiology department of Agha Khan University involving 239 children less than 16 years with clinically suspected appendicitis referred to radiology department from January 2009 to October 2011 were included. Medical records were reviewed for patient demographics, presenting signs and symptoms, sonographic, surgical findings and histopathological results. Results Two hundred and thirty nine patients with clinical suspicion of appendicitis were referred for focused ultrasound for appendix. Ultrasound examination showed 59 cases (24.6%) positive for appendicitis and thus they were operated. All of these were positive on histopathology. The remaining 180 cases (75.4%) that were negative on U/S were managed conservatively. Out of these 180 cases, 13 patients with negative findings on imaging studies were later operated due to clinical decision and/or CT examination. Acute appendicitis was proven in 10 out of the 13 cases. Conclusion Focused ultrasound has high sensitivity in acute appendicitis for the assessment of clinically equivocal cases of pediatrics population. It can be used as an initial screening modality especially in pediatric population, thus reducing additional cost and radiation risk associated with CT scans and also reducing rate of negative surgery.